Alexander Hamilton and the Development of American Law - Brown, Kate Elizabeth (Katherine Elizabeth) (Book collections on Project MUSE., 2017)
Alexander Hamilton never handed down decisions from a Supreme Court bench, nor did he write influential treatises on law. Yet he became the central figure in the development of American law in the early republic. Hamilton's authority over the formation of a republican jurisprudence both fit for a newly independent nation and compliant with the recently ratified Constitution was extensive; he transformed inherited imperial law into legal and constitutional principles befitting the American experiment in government, one that aimed to divide sovereignty among a central national government, individual states, and the American people